Large-scale monitoring and ecological risk assessment of persistent toxic substances in riverine, estuarine, and coastal sediments of the Yellow and Bohai seas. (April 2020) - Yoon, Seo Joon; Hong, Seongjin; Kim, Seonju; Lee, Jongmin; Kim, Taewoo; Kim, Beomgi; Kwon, Bong-Oh; Zhou, Yunqiao; Shi, Bin; Liu, Peng; Hu, Wenyou; Huang, Biao; et al.
Graphical abstract: Highlights: Target PAHs, APs, and SOs were detected in all sediments from Yellow and Bohai seas. Industrial and municipal activities significantly correlated to increased PAHs pollution. Sources of PAHs in China shifted from multiple to diesel and gasoline combustion recently. Great potential ecological risk was found in Nantong, Huludao, and Qinhuangdao in China. Chemicals and/or sites of concern varied between China and South Korea and across regions. Abstract: The Yellow and Bohai seas comprise one of the most rapidly developing regions in the world, but efforts to assess coastal pollution by persistent toxic substances (PTSs) on wide spatial scale are lacking. The present study aimed to (1) measure the concentrations of PTSs, such as polycyclic aromatic hydrocarbons (PAHs), alkylphenols (APs), and styrene oligomers (SOs) via large-scale sediment monitoring (total of 125 locations), (2) assess potential ecological risk of PTSs in sediments to coastal ecosystems, (3) estimate various sources and fresh inputs of PTSs, (4) determine distribution patterns of PTSs by human activities and land-use type, and (5) address decadal (2008–2018) changes in distributions of PTSs. The high concentrations of PAHs [> 7000 ng g −1 dry weight (dw)] in sediments were detected in Nantong in the Yellow Sea of China (YSC) and Huludao and Qinhuangdao in the Bohai Sea (BS), whereas lesser concentrations (< 200 ng g −1 dw) were detected in the Yellow Sea of Korea (YSK). We found relatively high concentrations of sedimentary APs and SOs in Nantong, Huludao, and Qinhuangdao from the YSC and BS regions, but corresponding concentrations were generally below < 100 ng g −1 dw in other locations. Concentrations of PAHs at 38 locations (30% of YSC and BS) posed a potential risk to aquatic ecosystems, whereas relatively low risk concentrations occurred in all locations of YSK. The main source of PAHs (concentrated in YSC and BS) were by-products of diesel and gasoline combustion (42% of total concentration), whereas biomass combustion (24%) dominated in YSK. Fresh inputs of PTSs indicated that the generation and use of PTSs continue across all regions and locations. Among PTSs, concentrations of PAHs were significantly associated with location ( p < 0.05) relative to land-use within a given region, whereas concentrations of APs and SOs showed no significant relationships ( p > 0.05) among or within regions. Over time, concentrations of PAHs have generally declined, but sediment contamination has increased at some locations in China, with sources shifting from a mixture of PAHs types to those linked to diesel and gasoline combustion. Additional studies are needed on the fate and potential ecological risk posed by certain PTSs in hotspots. This is one of the first efforts providing backgrounds on PTS pollution in the large marine ecosystem of the Yellow and Bohai seas.